High Throughput Method for Analysis of Repeat Number for 28 Phase Variable Loci of Campylobacter jejuni Strain NCTC11168. - Lea Lango-Scholey; Jack Aidley; Alexandra Woodacre; Michael A Jones; Christopher D Bayliss (PLoS ONE)
Mutations in simple sequence repeat tracts are a major mechanism of phase variation in several bacterial species including Campylobacter jejuni. Changes in repeat number of tracts located within the reading frame can produce a high frequency of reversible switches in gene expression between ON and OFF states. The genome of C. jejuni strain NCTC11168 contains 29 loci with polyG/polyC tracts of seven or more repeats. This protocol outlines a method-the 28-locus-CJ11168 PV-analysis assay-for rapidly determining ON/OFF states of 28 of these phase-variable loci in a large number of individual colonies from C. jejuni strain NCTC11168. The method combines a series of multiplex PCR assays with a fragment analysis assay and automated extraction of fragment length, repeat number and expression state. This high throughput, multiplex assay has utility for detecting shifts in phase variation states within and between populations over time and for exploring the effects of phase variation on adaptation to differing selective pressures. Application of this method to analysis of the 28 polyG/polyC tracts in 90 C. jejuni colonies detected a 2.5-fold increase in slippage products as tracts lengthened from G8 to G11 but no difference between tracts of similar length indicating that flanking sequence does not influence slippage rates. Comparison of this observed slippage to previously measured mutation rates for G8 and G11 tracts in C. jejuni indicates that PCR amplification of a DNA sample will over-estimate phase variation frequencies by 20-35-fold. An important output of the 28-locus-CJ11168 PV-analysis assay is combinatorial expression states that cannot be determined by other methods. This method can be adapted to analysis of phase variation in other C. jejuni strains and in a diverse range of bacterial species.